Impact of co-payment level increase of antidiabetic medications on glycaemic control: an interrupted time-series study among Finnish patients with type 2 diabetes - Piia Lavikainen; Emma Aarnio; Kari Jalkanen; Hilkka Tirkkonen; Päivi Rautiainen; Tiina Laatikainen; Janne Martikainen (BMC, 2020)
Abstract Background A new special reimbursement scheme (SRS) for non-insulin medications used for treatment of hyperglycaemia in type 2 diabetes (T2D) was implemented in Finland on January 1, 2017. The new SRS affected all community-dwelling Finnish T2D patients as all community-dwelling residents are eligible for reimbursement for prescription medications. The aim of the study was to evaluate the impact of this co-payment increase on glycaemic control among Finnish T2D patients. Methods Data on glycaemic control were collected with HbA1c measures from electronic health records from primary health care and specialized care in the North Karelia region, Finland, from patients with a confirmed T2D diagnosis in 2012 who were alive on January 1, 2017 (n = 8436). Average HbA1c levels were measured monthly 36 months before and 33 months after the policy change. Consumption of diabetes medications was measured with defined daily doses (DDDs) based on reimbursed medication purchases. Interrupted time series design analysed with segmented regression model was applied to examine the effect of the policy change on average HbA1c levels. Results Eight thousand one hundred forty-three T2D patients had at least one HbA1c measurement within 01/2014-9/2019. Mean age of the patients was 68.1 (SD 11.3) years and 53.0% were women. Average time since T2D diagnosis was 11.5 (SD 6.1) years. An estimated increase of 0.81 (95% confidence interval, CI, 0.04-1.58) mmol/mol in average HbA1c levels was detected at the time of the policy change. In subgroup analyses, strongest effects were detected among patients who used only other diabetes medications than insulin or metformin in 2016 (3.56 mmol/mol, 95% CI 2.50-4.62). Meanwhile, yearly consumption of diabetes medications decreased slightly from 618.9 (SD 487.8) DDDs/patient in 2016 to 602.9 (SD 475.6) DDDs/patient in 2017 (p = 0.048). Conclusions Simultaneously with the increase of the co-payment level, the average HbA1c level increased among T2D patients from the North Karelia region, Finland. This may be explained by the decreased consumption of diabetes medications between 2016 and 2017. Special attention should be allocated to glycaemic control of patients utilizing only other antidiabetic medications than metformin or insulin.